2007
DOI: 10.2134/agronj2006.0132
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cropping Systems for Sustainable Crop Production in the Northern Great Plains

Abstract: Producers need to know how to sequence crops to develop sustainable dynamic cropping systems that take advantage of inherent internal resources, such as crop synergism, nutrient cycling, and soil water, and capitalize on external resources, such as weather, markets, and government programs. The objective of our research was to determine influences of previous crop and crop residues (crop sequence) on relative seed and residue yield and precipitation-use efficiency (PUE) for the no-till production of buckwheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 10 publications
4
80
0
1
Order By: Relevance
“…Except for the 2000/01 season with its extremely low January rainfall, RUEs of maize correspond well with values reported from elsewhere on the Highveld (Bennie et al, 1995), calculated from available data (Nel et al, 2003; and reported for the semi-arid areas of North America (Eck & Winter, 1992;Varvel, 1994;Norwood, 1999;Tanaka et al, 2007;). The rainfall use efficiency of the monoculture maize was relatively high and with the exception of maize preceded by groundnut, equal to that of maize grown in rotation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Except for the 2000/01 season with its extremely low January rainfall, RUEs of maize correspond well with values reported from elsewhere on the Highveld (Bennie et al, 1995), calculated from available data (Nel et al, 2003; and reported for the semi-arid areas of North America (Eck & Winter, 1992;Varvel, 1994;Norwood, 1999;Tanaka et al, 2007;). The rainfall use efficiency of the monoculture maize was relatively high and with the exception of maize preceded by groundnut, equal to that of maize grown in rotation.…”
Section: Discussionsupporting
confidence: 88%
“…In six of the nine seasons included in this experiment the annual rainfall was outside these thresholds (Table 1) Rainfall use efficiency (RUE) was calculated as grain yield produced per increment of precipitation (Tanaka et al, 2007) using the accumulated rainfall from 1 July to 30 June for each season. Analysis of variance was performed to determine whether significant differences existed among the yield and RUE of …”
Section: Methodsmentioning
confidence: 99%
“…Pea, being a legume, fixes N from the atmosphere and had higher N concentration than spring wheat or barley (Lenssen et al 2007b;Sainju et al 2009). Other benefits of crop diversification include effective control of weeds, diseases, and pests (Vigil et al 1997;Miller et al 2002;Tanaka et al 2002), reduction in the risk of crop failure, farm inputs, and duration of fallow, and improvement in economic and environmental sustainability (Matson et al 1997;Gregory et al 2002). Although SOC and STN are influenced by the quality and quantity of crop residue returned to the soil (Campbell et al 1992;Kuo et al 1997;Sainju et al 2009), limited information exists on the effect of diversified crop rotations on soil organic matter in NT and CT practices in dryland cropping systems.…”
Section: Introductionmentioning
confidence: 99%
“…Given this context, NGPRL scientists used a novel crop by crop residue matrix study design to investigate 100 different crop sequences for their residual effects on grain yield, pests (diseases, weeds, and insects), soil water use, and soil properties (Krupinsky et al 2006;Tanaka et al 2007) (figure 2). This research spurred the development of the dynamic cropping systems concept, whereby crop sequence decisions are made annually in order to optimize production, economic, and resource conservation goals (Tanaka et al 2002). Successful application of the dynamic cropping system concept has been considered essential for increasing adaptability to high-risk conditions ) and may therefore …”
Section: Major Research Accomplishmentsmentioning
confidence: 99%
“…The Crop Sequence Calculator (CSC), a farmer-friendly, interactive software program to design productive and profitable crop sequences, was developed in the early 2000s using results from crop rotation research (Tanaka et al 2002). In 2009, the Cover Crop Chart (CCC) was developed by NGPRL scientists and staff in response to the growing demand for userfriendly cover crop information .…”
Section: Figurementioning
confidence: 99%